2019
DOI: 10.1021/acs.inorgchem.9b01060
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Aqueous CO2 Reduction Using a Pyrene-Modified Rhenium(I) Diimine Complex

Abstract: The development of molecular catalysts and materials that can convert carbon dioxide (CO2) into a value-added product is a great chemical challenge. Molecular catalysts set benchmarks in catalyst investigation and design, but their incorporation into solid-state materials, and optimization of the electrochemical operating conditions, is still needed. For example, rhenium­(I) diimine catalysts show almost quantitative selectivity for the conversion of CO2 to carbon monoxide (CO) in acetonitrile (MeCN), but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…This work clearly demonstrates the utility of organic chromophore electron reservoirs to effectively lower the overpotential required for CO 2 reduction for Re­(bpy) complexes. Operation of these molecular electrocatalysts at lower overpotentials not only decreases the required energetic input but also may improve system longevity. , Moreover, these chromophores may serve as useful electrode anchoring units (i.e., through π-stacking), a strategy that is well-known to simultaneously increase catalyst activity and longevity. A combination of these concepts of diminished overpotential and improved catalyst stability together may afford the prospect of developing industrially feasible devices. , Given the abundance of photoactive π-conjugated chromophores, an opportunity exists to systematically synthesize a variety of supramolecular dyad CO 2 reduction catalysts that have tailored properties to maximize performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work clearly demonstrates the utility of organic chromophore electron reservoirs to effectively lower the overpotential required for CO 2 reduction for Re­(bpy) complexes. Operation of these molecular electrocatalysts at lower overpotentials not only decreases the required energetic input but also may improve system longevity. , Moreover, these chromophores may serve as useful electrode anchoring units (i.e., through π-stacking), a strategy that is well-known to simultaneously increase catalyst activity and longevity. A combination of these concepts of diminished overpotential and improved catalyst stability together may afford the prospect of developing industrially feasible devices. , Given the abundance of photoactive π-conjugated chromophores, an opportunity exists to systematically synthesize a variety of supramolecular dyad CO 2 reduction catalysts that have tailored properties to maximize performance.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of combustion products (i.e., CO 2 , H 2 O) back to chemical precursors and fuels using electrons derived from renewable resources is one viable path toward lowering carbon emissions and closing the carbon loop. , In theory, solar radiation provides enough energy to perform these thermodynamically and kinetically uphill chemical reactions but, in practice, catalysts are required to enable efficient product delivery. , While heterogeneous electrocatalysts are favored for their scalability and facile device integration, these materials often suffer from a lack of product selectivity. Although improvements have been made, the rational design of molecular catalysts affords a more systematic method to tune and improve catalyst activity and product selectivity. Though most molecular catalysts still require a high overpotential to drive electrocatalytic CO 2 reduction, issues concerning the durability of these systems can often be resolved by immobilizing these molecular catalysts. Thus, for these catalysts to be employed in robust, industrially relevant devices that are energy efficient, catalyst design should emphasize the importance of accomplishing these chemical processes at the lowest overpotential possible. , …”
Section: Introductionmentioning
confidence: 99%
“…A similar approach has been pursued with redoxactive thiophene units in the backbone. 6 Recently, a different strategy has been investigated: pyrene groups, which undergo π-interactions with carbonic materials, have been introduced in the ligand backbone in order to adsorb the catalyst onto the surface of carbon black 7 or edge-plane graphite 8 electrodes. The modified carbon black material was moderately active in MeCN with a faradaic yield of 70% for CO. 7 Immobilized catalysts on carbonous materials offer the advantage to use water, in which α-diimine-Re(CO) 3 complexes are usually not soluble, instead of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The modified carbon black material was moderately active in MeCN with a faradaic yield of 70% for CO. 7 Immobilized catalysts on carbonous materials offer the advantage to use water, in which α-diimine-Re(CO) 3 complexes are usually not soluble, instead of organic solvents. 8,9 Warren and co-workers showed that such modified electrodes are active for CO 2 -to-CO reduction in water and exhibit high TON. 8 This was rather unexpected as the complexes were inactive in organic solvent mixtures and thus, the heterogenisation turned an inactive complex into an active catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation